PENERAPAN KEBIJAKAN INSENTIF GREEN BUILDING DI KOTA BANDUNG - Jemy Ronald Nehemia Pahnael; Anton Soekiman; Mia Wimala (Jurnal Infrastruktur, 2020)
Bandung is the first city in Indonesia that has issued its regulations on green building incentives, i.e. gross floor area concessions, and tax deduction. Since 2016, the local government has never conducted a monitoring and evaluation of the practice of these regulations. Therefore, this study aims to determine the extent of the implementation of green building incentives in Bandung. By knowing the problems, the strategy oh improvement can be formulated thoroughly. Data collection was done through in-depth interviews with respondents who have a direct link to the implementation of green building policies in Bandung, including the City Spatial Planning Agency (Distaru), The Investment Board One Stop-Service (DPMPTSP), Regional Revenue Management Agency (BPPD), Building Expert Team (TABG) and Regulatory Drafting Team concerning Green Buildings. The results show that so far there has been no incentive issued by the mayor because no building has met the green building requirements of 2 and 3-star by current regulations. The results also obtained that the existing regulations do not regulate the amount, form, awarding time, and the validity period/duration in detail. Therefore, despite meeting the requirements, the building owner/developer cannot propose any green building incentives. Several recommendations are the socialization program that must be carried out on the government, as well as the community, and further regulations governing the details of incentive policies must be designed and issued as soon as possible.